Complementary massage therapy intervention for hypertensive patients to lower blood pressure: A case study - Oktarisa, Yunika; Budianto, Yudi (Science Center Group, 2024)
Background: Hypertension remains a major public health problem that contributes to cardiovascular morbidity and mortality worldwide. Pharmacological therapy is widely used to control blood pressure, yet many patients continue to experience symptoms such as headache and psychological stress. Complementary interventions including massage therapy have gained attention because they promote relaxation and improve cardiovascular regulation. Objective: This study aimed to explore the implementation of complementary massage therapy intervention for hypertensive patients to lower blood pressure through a nursing case study approach. Methods: This study used a case study design following the CARE guideline from the EQUATOR Network. Two hypertensive patients who received nursing care at Puskesmas Tanjung Baru in 2022 were included. Nursing care followed the nursing process including assessment, nursing diagnosis, intervention, implementation, and evaluation. The complementary intervention consisted of Swedish massage therapy applied for 20–30 minutes. Blood pressure and clinical indicators were measured before and after the intervention using standard vital sign monitoring procedures. Results: The intervention showed improvements in blood pressure and clinical symptoms in both patients. Patient A demonstrated a reduction in blood pressure from 160/90 mmHg to 140/90 mmHg, while Patient B experienced a decrease from 150/90 mmHg to 130/80 mmHg. Both patients also reported reductions in headache intensity and improved relaxation following the intervention. Conclusion: Complementary massage therapy appears to provide beneficial effects in lowering blood pressure and reducing symptoms among hypertensive patients. This intervention may serve as a supportive nursing strategy in primary healthcare settings to enhance holistic hypertension management.